Differences in The Application of Conceptual Understanding Procedures Model (CUPs) and Concept Attainment Model (CAM) on Students Misconception Reduction in Digestive System Material - Dewi, Shelena Nugraha R; Nilawarni, Reduk; Rusdi, R (Universitas Negeri Jakarta, 2015)
Students require depth understanding of the concept on dygestive system material, however misconception often happens so that optimal learning isn’t reached. This needs to be taken seriously. The introduction and implementation of Conceptual Understanding Procedures Model (CUPs) and Concept Attainment Model (CAM) are expected to reduce the misconception occur in students. Both models are learning model that requires the involvement and student activity in the learning process and can encourage students to be able to construct a concept. This study aimed to obtain data about differences in the application of CUPs and CAM on student misconception reduction in digestive system material. The research was conducted in SMAN 61 Jakarta on February-March 2015. The reseach method used was a quasi experiment. The research sample obtained after pretest ware students who have misconception on XI MIA 2 (The 1st experimental class with CUPsmodel) and XI MIA 4 (The 2nd experimental class with CAM) who collected by simple random sampling. The instrumen used was a multiple choice objective test accompanied by CRI index. Prerequisite test analysis of normality was the Kolmogorov-Smirnov and homogeneity test with the F test. Based on calculation, data obtained was not normally distributes but homogeneous. The statistical hypothesis with Mann-Whitney test result on accepted null ypothesis at α 0,05. It showed that there was no differences in the application of CUPs model and CAM on student’s misconception reduction in digestive system material.